Induced Rate Performance Enhancement in Off‐Stoichiometric Na3+3xV2−x(PO4)3 with Potential Applicability as the Cathode for Sodium‐Ion Batteries. Issue 30 (8th May 2017) - Aragón, María J.; Lavela, Pedro; Ortiz, Gregorio F.; Alcántara, Ricardo; Tirado, José L.
Abstract: Off‐stoichiometric Na3+3 x V2− x (PO4 )3 samples have been prepared by a sol‐gel route. X‐ray diffraction and XPS revealed the flexibility of the NASICON framework to accommodate these deviations of the stoichiometry; at least for low x values. X‐ray photoelectron spectra evidenced the presence of Na4 P2 O7 impurities. The synergic combination of the structural deviations and the presence of Na4 P2 O7 impurities induce a significant improvement of the electrochemical performance and cycling stability at high rates, as compared to the stoichiometric Na3 V2 (PO4 )3 sample. The fast kinetic response provided by the induced off‐stoichiometry involves a decrease of the cell resistance. Abstract : Useful impurities : The synergic combination of the structural deviations and the presence of the amorphous pyrophosphate impurity in off‐stoichiometric Na3+3 x V2− x (PO4 )3 /C induce a significant improvement of the electrochemical performance as positive electrode for Na‐ion batteries.